Effect of a web drama video series on HIV and other sexually transmitted infection testing among gay, bisexual and queer men: study protocol for a community-based, pragmatic randomised controlled trial in Singapore: the People Like Us (PLU) Evaluation Study. Issue 4 (7th April 2020) - Tan, Rayner Kay Jin; Koh, Wee Ling; Le, Daniel; Tan, Avin; Tyler, Adrian; Tan, Calvin; Banerjee, Sumita; Wong, Chen Seong; Wong, Mee-Lian; Chio, Martin Tze-Wei; Chen, Mark I-Cheng
Abstract : Introduction: Gay, bisexual and queer (GBQ) men are at disproportionately higher risk of acquiring HIV and other sexually transmitted infections (STI). While HIV/STI testing rates among GBQ men are increasing worldwide, they remain suboptimal in a variety of settings. Methods and analysis: The study is a pragmatic randomised controlled trial designed to evaluate an online video series developed by a community-based organisation in Singapore for GBQ men. A total of 300 HIV-negative GBQ men in Singapore aged 18–29 years old will be recruited for this study. Participants will subsequently be randomised into the intervention arm (n=150) and the control arm (n=150). The intervention arm (n=150) will be assigned the intervention along with sexual health information via a pamphlet, while the control group (n=150) will be assigned only the sexual health information via a pamphlet. Participants should also not have watched the video prior to their participation in this study, which will be ascertained through a questionnaire. Primary outcomes for this evaluation are changes in self-reported intention to test for, actual testing for and regularity of testing for HIV, syphilis, chlamydia and gonorrhoea at the 3 and 6 months after intervention. Secondary outcomes include changes in self-reported risk perception for HIV and other STIs, knowledge of HIV, knowledge of risks associated with acquiring STIs, knowledge of HIV pre-exposure prophylaxis, consistent condom use for anal sex with casual partners, incidence of STIs, connectedness to the lesbian, gay, bisexual and transgender community, self-concealment of sexual orientation, perceived homophobia, internalised homophobia, HIV testing self-efficacy and HIV testing social norms. Ethics and dissemination: The study has been approved by the National University of Singapore Institutional Review Board (S-19-059) and registered at ClinicalTrials.gov. The results will be published in peer-reviewed academic journals and disseminated to community-based organisations and policymakers. Trial registration number: NCT04021953